Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Certainly! Let's solve the equation step-by-step using cross multiplication.
Given the equation:
[tex]\[ \frac{3x - 3}{5} = \frac{2x - 2}{4} \][/tex]
Step 1: Cross-multiply both sides to eliminate the fractions.
This means we multiply the numerator on the left by the denominator on the right, and the numerator on the right by the denominator on the left:
[tex]\[ 4 \cdot (3x - 3) = 5 \cdot (2x - 2) \][/tex]
Step 2: Distribute the numbers on both sides of the equation:
[tex]\[ 4 \cdot 3x - 4 \cdot 3 = 5 \cdot 2x - 5 \cdot 2 \][/tex]
[tex]\[ 12x - 12 = 10x - 10 \][/tex]
Step 3: Move all terms involving [tex]\( x \)[/tex] to one side of the equation and constant terms to the other side. We start by subtracting [tex]\( 10x \)[/tex] from both sides:
[tex]\[ 12x - 10x - 12 = 10x - 10x - 10 \][/tex]
[tex]\[ 2x - 12 = -10 \][/tex]
Step 4: Add 12 to both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 2x - 12 + 12 = -10 + 12 \][/tex]
[tex]\[ 2x = 2 \][/tex]
Step 5: Divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{2}{2} \][/tex]
[tex]\[ x = 1 \][/tex]
Thus, the solution to the equation is:
[tex]\[ x = 1 \][/tex]
Given the equation:
[tex]\[ \frac{3x - 3}{5} = \frac{2x - 2}{4} \][/tex]
Step 1: Cross-multiply both sides to eliminate the fractions.
This means we multiply the numerator on the left by the denominator on the right, and the numerator on the right by the denominator on the left:
[tex]\[ 4 \cdot (3x - 3) = 5 \cdot (2x - 2) \][/tex]
Step 2: Distribute the numbers on both sides of the equation:
[tex]\[ 4 \cdot 3x - 4 \cdot 3 = 5 \cdot 2x - 5 \cdot 2 \][/tex]
[tex]\[ 12x - 12 = 10x - 10 \][/tex]
Step 3: Move all terms involving [tex]\( x \)[/tex] to one side of the equation and constant terms to the other side. We start by subtracting [tex]\( 10x \)[/tex] from both sides:
[tex]\[ 12x - 10x - 12 = 10x - 10x - 10 \][/tex]
[tex]\[ 2x - 12 = -10 \][/tex]
Step 4: Add 12 to both sides to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 2x - 12 + 12 = -10 + 12 \][/tex]
[tex]\[ 2x = 2 \][/tex]
Step 5: Divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{2}{2} \][/tex]
[tex]\[ x = 1 \][/tex]
Thus, the solution to the equation is:
[tex]\[ x = 1 \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.